SFas and FasL in etiopathogenesis of autoimmune diseases of the thyroid gland and nodular forms of goiter - Sheremet, M. I.; Shidlovskyy, V. O.; Girla, Y. V.; Tkachuk, N. P.; Tibirna, A. G.; Dorosh, V. P. (Journal of Education, Health and Sport, 2015)
Sheremet М. І., Shidlovskyy V. О., Girla Y. V., Tkachuk N. P., Tibirna A. G., Dorosh V. P. SFas and FasL in etiopathogenesis of autoimmune diseases of the thyroid gland and nodular forms of goiter. Journal of Education, Health and Sport. 2015;5(12):41-49. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34845 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A41-49 http://pbn.nauka.gov.pl/works/675989 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015. SFAS AND FASL IN ETIOPATHOGENESIS OF AUTOIMMUNE DISEASES OF THE THYROID GLAND AND NODULAR FORMS OF GOITER М. І. Sheremet, V. О. Shidlovskyy*, Y. V. Girla, N. P. Tkachuk, A. G. Tibirna*, V. P. Dorosh Bukovinyan State Medical University, Chernivtsy, Ukraine *I.Y. Horbachevsky State Medical University, Ternopol, Ukraine *PhD, assistant professor, USMF , Nicolae Testemiţanu” Chisinau, Moldova Abstract The objective of this research was to check whether the apoptotic inhibitor sFas (soluble fibroblaste-assosiated cell surface) and the apoptotic inducer FasL (fibroblaste-assosiated cell surface ligand) are differentially present in two opposite phenotypes of autoimmune thyroid disorders (AITD) and nodular goiter (NG). However, in contrast to GD (Graves’ disease), decreased sFas in HT (Hashimoto’s thyroiditis) increased FasL, indicate destruction of thyrocytes. In cases of thyroid NG, sFas may provide a key protective signal that helps the cells to avoid apoptosis in a hostile environment. Keywords: Autoimmune thyroid disease, Fas ligand, soluble Fas, Graves’ disease, Hashimoto’s thyroiditis, nodular goiter.